Impact of Different Ovarian Stimulation Protocols on Thyroid Hormone Levels: A Prospective Cohort Study: Dampak dari Protokol Stimulasi Ovarium yang Berbeda terhadap Kadar Hormon Tiroid: Sebuah Studi Kohort Prospektif - Al-Azzawi, Buthainah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Ovarian stimulation is pivotal in assisted reproductive technologies, yet its systemic hormonal effects—particularly on thyroid function—remain underexplored. Specific Background: Estrogen-induced increases in thyroxine-binding globulin and the structural mimicry between hCG and TSH suggest a complex thyroid-ovarian interaction. Knowledge Gap: Prior studies yield conflicting evidence on thyroid hormone alterations during stimulation, with limited attention to regimen-specific effects and longitudinal dynamics in thyroid-naïve women. Aim: This study investigates the temporal impact of distinct ovarian stimulation protocols—Clomid, Pergonal, and their combination—on thyroid hormone levels in euthyroid infertile women. Results: A significant elevation in TSH and reduction in T3/T4 was observed as early as month one in the combination group, month two in the Pergonal group, and month three in the Clomid group (P<0.05). Novelty: This study delineates protocol- and time-dependent thyroid disturbances, offering mechanistic clarity on drug-specific endocrine crosstalk. Implications: Findings support tailored thyroid monitoring during ART and propose a stratified approach based on stimulation regimen and exposure duration to prevent potential subclinical hypothyroidism and optimize fertility outcomes.Highlights: Combination therapy (Clomid + Pergonal) caused the earliest and most significant thyroid disruption-elevated TSH and decreased T3/T4 from Month 1. Thyroid dysfunction varied by stimulation protocol: Clomid-only showed delayed effects (Month 3), while Pergonal-only effects began in Month 2. Clinical recommendation: Thyroid monitoring is crucial during ovarian stimulation, especially with combination regimens. Keywords: Ovarian Stimulation, Clomiphene Citrate, Pergonal, Thyroid hormones, Infertility